Financial constraints, ownership dilution, and the method of payment in M&A transactions - de Bodt, Eric; Cousin, Jean-Gabriel; Officer, Micah S. (Journal of Corporate Finance, 2022)
The method of payment choice in merger and acquisition (M&A) transactions has been the subject of much research in the finance literature. But significant changes in the economic environment of acquirers in the U.S. call into question whether known stylized facts are still valid and motivate us to undertake new empirical analyses. Using a large sample of M&A transactions spanning the last two decades, we investigate the financial constraints versus ownership dilution tradeoff that potentially drives negotiations about the method of payment (i.e., stock or cash), controlling for an extensive list of other potential determinants. The main takeaway from our analyses is that financial constraints are a dominant factor motivating acquirers to include stock (at least partially) in the method of payment package in M&A transactions in the recent period.